(untitled) (The Review of Diabetic Studies, 2025)
This research intends to characterize the fact of the management of the cardiac arrest cases prior to the hospitalization in the Saudi Red Crescent Authority. The research paper will use a descriptive approach, where it will only review and analyze earlier studies, academic research, scientific research, and official reports on pre-hospital emergency medical services and management of cardiac arrest cases. There were no field survey, experimental or direct data collection instruments. The study area of interest is to detail the existing procedures used by Saudi Red Crescent paramedics in responding to the cardiac arrest cases within the pre-hospital environment, emergency response operations, first patient evaluation, cardiopulmonary resuscitation (CPR) and automated external defibrillators (AEDs), as well as communication with the hospitals of receiving. Besides, the paper outlines the key issues and limitations that have been outlined by other literature sources, including response time, equipment availability, the degree of professional training, community knowledge of emergency response, and logistical and environmental considerations that can influence patient outcomes. The research provides a robust representation of the existing reality of the pre-hospital cardiac arrest management at the Saudi Red Crescent through both the analysis and synthesis of the current studies. The conclusions of this descriptive review should help improve the awareness of the strengths and gaps in the existing practice and assist a decision-maker/healthcare planner to increase the efficiency and quality of pre-hospital emergency medical services, which would, in turn, help to improve the survival rates and patient outcomes in cases of cardiac arrest